Neural image and video captioning (NIVC) - Lee, Jeremy Kian Kiat (Nanyang Technological University, 2022)
A common problem linking computer vision and natural language processing is the ability to generate accurate captioning for a given image. Researchers have spent decades trying to perfect the state of art image captioning.